Personalization independent teaching and learning of high school students as relevant didactic problem (Pedagogy of Higher and Secondary Education, 2013)
Bugra A. V. Personalization independent teaching and learning of high school students as relevant didactic problem.The article presents a review of the evolution of pedagogical views on the problem of individualization of learning, the necessity of developing didactic framework of the principle of individual and differentiated approach to the students in the process of self-learning and cognitive activity.
Keywords: self-training and cognitive activity; personalization; differentiation; individual and differentiated approach